Standardisation Of Precast Concrete Members For Low-Rise Residential Framed Building - Heng, Chiang Chew (2002)
Precast concrete technology has become an emerging trend in Malaysian Construction Industry. Hence, there is a niche in developing a set of standardised and optimised precast concrete elements as well as connections for a speedy, affordably and better quality residential building. By studying the preferred sizes of the structural members in the existing and combined with the standards of Modular Coordination System; the standardization of precast concrete elements for skeletal framing type of structure can be achieved. This thesis had also covered the economy part of the elements by comparing the costs of producing these elements for different sets of dimension and reinforcement combinations until deriving to a most cost effective section with the respective span. Nearly 300 types of precast concrete elements and connections that have been standardised and optimised through the above mentioned process for skeletal framing residential structures. This is to streamline the precast concrete industry towards proper metrication and cost efficiency in planning, design, construction, assembly and manufacturing of these elements and joints. Case study on application of standardised precast elements and connections of a residential building - Putra Apartment has proven the practicability of these elements and connections in the building.